Answer:
4 ÷ 5/6
= 4 × 6/5
= 24/5
= 4 4/5
Hope this helps.
Which function has a vertex at the origin?
A f(x) = (x + 4)2
B fx) = x(x - 4)
C f(x) = (x - 4)(x + 4)
D f(x)= x²
answer D
Step-by-step explanation:
Hello,
we can check the graph of the functions as attached or compute the vertex analytically
from the graph you can see that D is the correct answer
In a bag there are 3 red marbles, 2 yellow marbles, and 1 blue marble. What is the likelihood of a yellow marble being selected on the first draw?
Answer:
1/3
Step-by-step explanation:
there's 6 total marbles and 2 are yellow so this can be expressed as 2/6 which can be simplified to 1/3.
hope it helps!
Answer:
1/3
Step-by-step explanation:
The total number of marbles
3 red marbles, 2 yellow marbles, and 1 blue marble = 6 marbles
P( yellow) = yellow / total
= 2/6
= 1/3
I need help on my algebra. :)
Answer:
Option B
Step-by-step explanation:
Consider the steps below;
[tex]3x - 4y = 25,\\3x + 2y = 1\\\\3x - 4y = 25,\\+ ( - 3x - 2y = - 1 )\\\\- 6y = 24,\\y = - 4\\\\3x - 4y = 25,\\3x - 4 * ( - 4 ) = 25,\\3x + 16 = 25,\\3x = 9,\\x = 3\\\\Solution, x = 3, y = - 4[/tex]
To solve this system of equations, I applied process of elimination, which I thought was most convenient. Multiplying the bottom equation by - 1, I added both equations to cancel out the x's and solved for the value of y. Substituting this value of y into the top equation, I solved for the value of x;
Solution ⇒ Option B
Verify sin^4 x - sin^2 x = cos^4 x - cos^2 x is an identity
Answer:
(identity has been verified)
Step-by-step explanation:
Verify the following identity:
sin(x)^4 - sin(x)^2 = cos(x)^4 - cos(x)^2
sin(x)^2 = 1 - cos(x)^2:
sin(x)^4 - 1 - cos(x)^2 = ^?cos(x)^4 - cos(x)^2
-(1 - cos(x)^2) = cos(x)^2 - 1:
cos(x)^2 - 1 + sin(x)^4 = ^?cos(x)^4 - cos(x)^2
sin(x)^4 = (sin(x)^2)^2 = (1 - cos(x)^2)^2:
-1 + cos(x)^2 + (1 - cos(x)^2)^2 = ^?cos(x)^4 - cos(x)^2
(1 - cos(x)^2)^2 = 1 - 2 cos(x)^2 + cos(x)^4:
-1 + cos(x)^2 + 1 - 2 cos(x)^2 + cos(x)^4 = ^?cos(x)^4 - cos(x)^2
-1 + cos(x)^2 + 1 - 2 cos(x)^2 + cos(x)^4 = cos(x)^4 - cos(x)^2:
cos(x)^4 - cos(x)^2 = ^?cos(x)^4 - cos(x)^2
The left hand side and right hand side are identical:
Answer: (identity has been verified)
The recipe calls for 5 cups of strawberries for every 3 cups of whipped cream. Write this comparison as a ratio. A. 5:3 B. 3:5 C. 5>3 D.
Answer: the answer is A 5:3
Step-by-step explanation:
Find the distance of point U(2, 3) from point V(5, 7).
Answer:
5
Step-by-step explanation:
You can draw a point at (5,3) and call it point A.
Connect point A with V and U to get VA = 4 and UA = 3.
You get a right triangle and use pythagoream theroem. The answer is the root of 4^2 + 3^2 which equals to 5.
The answer is 5
Two similar cylinders have radii of 28 inches and 32 inches. What is the ratio of their volumes?
Answer: A or B
Step-by-step explanation:
hey buddy
can we talk
⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀
NEED ANSWER ASAP. WILL MARK THE BRAINLIEST!
Answer: C) 4955.30
Step-by-step explanation:
Where: A = P(1 + r/n)nt
A= 4000 (1+0.055/1)1*4
A= 4000 x (1.055)^4
A= 4955.30
Will Give Brainilest If Correct:
True or False:
0 is neither positive or negative.
Answer:
true
Step-by-step explanation:
0 is one of the many things in life that make no sense.
// have a great day //
Answer:
True
Step-by-step explanation:
0 is like the barrier between positive and negative numbers.
So the answer is true.
whats a quadrilateral with two sides going in the same direction
Answer:
Trapezoid.
Step-by-step explanation:
That is a trapezoid ( in the UK a trapezium).
There is a pair of parallel sides.
please answer i need some help
Answer: - 1.10
Step-by-step explanation:
Point D is one space after -1 before -1.5.
Means it is at -1.10
PLSS HELP !!!A data set has a standard deviation of 2.5. The element 16 is an element of a data set, with a z-score of 2.4. What is the mean of the data set?
Answer:
10Step-by-step explanation:
Given the following parameters
standard deviation σ = 2.5
z-score Z = 2.4
observed value x = 16
Mean of the dataset μ = ?
Using the formula for calculating the z-score as shown to calculate the mean
[tex]Z = \frac{x - \mu}{\sigma}[/tex]
On substituting the values;
[tex]2.4 = \frac{16-\mu}{2.5} \\2.4 * 2.5 = 16-\mu\\6 = 16-\mu\\\mu = 16-6\\\mu = 10[/tex]
The mean of the dataset is 10
A cake recipe calls for 40 milliliters of water for every 20 milliliters of cooking
oil. How many milliliters of water are needed if 50 milliliters of cooking oil
were used?
O A) 25 ml
OB) 100 ml
O C) 200 ml
OD 1,000 ml
Answer:
B
Step-by-step explanation:
20x2 is 40, so 50x2 is 100
Answer:
BBBBBBBBBBBBBBBB
Step-by-step explanation:
5x2+3=0. find a=, b=, c=. thank you:)
Answer:
a=5 b=0 c=3
Step-by-step explanation:
The quadratic equation is written as
ax^2 + bx+c =0
5x^2 +3 =0
5x^2 +0x +3 =0
a=5 b=0 c=3
helppppoppooppppppppp.
Fabiola’s dog is 5 pounds heavier than one-third of the weight of Luisa’s dog. Fabiola’s dog weighs 23 pounds. Use the diagram to write an equation to represent the dogs’ weights. Let f represent the weight of Luisa’s dog. A long rectangle is the top section. 2 smaller rectangles are the bottom section. The top section represents . The bottom section represents . The equation is . ASAP PLEASE MARKING BRAINLIEST
Answer:
[tex]\frac{1}{3}[/tex]f + 5 = 23
Step-by-step explanation:
Let's put this statement into words: Fabiola’s dog is 5 pounds heavier than one-third of the weight of Luisa’s dog. Fabiola’s dog weighs 23 pounds.
This is an equation representing the weight of Fabiola's dog:
[tex]\frac{1}{3}[/tex]f + 5 = 23
I honestly have no idea what the diagram is supposed to mean, it'd be great if you could provide a picture :), then I'll edit my answer.
Answer:
The top section represents...........23 pounds
The bottom section represents..........5 + 1/3f
The equation is.........23 = 1/3f + 5
Step-by-step explanation:
Which of the following is the explicit rule for a geometric sequence defined by a recursive formula of an=5an-1 for which the first term is 23?
Answer:
D
Step-by-step explanation:
The explicit rule for a geometric sequence is
[tex]a_{n}[/tex] = a [tex]r^{n-1}[/tex]
where a is the first term and r the common ratio
Here a = 23 and from the recursive formula
[tex]a_{n}[/tex] = 5[tex]a_{n-1}[/tex] , then r = 5 , thus explicit formula is
[tex]a_{n}[/tex] = 23 × [tex]5^{n-1}[/tex] → D
The correct option is D.
The calculation is as follows:The explicit rule for a geometric sequence is
[tex]an = ar^{n-1}[/tex]
Here
a represents the first term
r represents the common ratio
So,
[tex]a_n = 5a_{n-1}[/tex]
So,
[tex]a_n = 23\times 5^{n-1}[/tex]
Learn more: brainly.com/question/17429689
i need help please....
Answer:
34
Step-by-step explanation:
area = (1/2)base * height.
area= half of 17 times 4
a=8.5 x 4
a=34
Answer: C
Step-by-step explanation:
Area = 1/2 bh
Area = 1/2 x 4 x 17
= 34 sq inches
Prove that the following statements are false provide counter examples to disprove them: (1) If two angles have common vertex and their bisectors create one line, then these angles are vertical. (2) If the angle bisectors of two equal angles belong to the same line, then these angles are vertical.
Answer:
Examples to disprove them are as follows;
1) Angles of two different inscribed regular polygon in contact at their vertices
2) Angles on the opposite corners of a regular even sided polygon
Step-by-step explanation:
The statement to be disproved can be presented as follows;
1) ∠A and ∠B share a common vertex
2) The bisectors of ∠A and ∠B create one line then
∠A and ∠B are vertical, that is ∠A and ∠B are on the opposite sides of the point where two lines cross or ∠A = ∠B
Given that ∠A = Interior angle of a inscribed square = 90°
∠B = Interior angle of an inscribed equilateral triangle = 60°
Therefore the two circles can be arranged such that the line connecting the centers of both circles, are the bisectors of ∠A and ∠B
However, ∠A ≠ ∠B hence the two angles are not vertical QED
(2) The angles ∠A and ∠B where ∠A = ∠B are on the opposite corners of an even sided regular polygon are equal and their bisectors belong to the same line, however, it can be shown that ∠A and ∠B are not vertical.
ANSWER ASAP IM GIVING BRAINLIEST!
The trapezoid is composed of a rectangle and two triangles. What is the area of the rectangle? What is the total area of the triangles? What is the area of the trapezoid?
A) 13 cm2; 15 cm2; 28 cm 2
B) 26 cm2; 15 cm2; 41 cm 2
C) 40 cm2; 15 cm2; 55 cm 2
D) 40 cm2; 7.5 cm2; 47.5 cm 2
Step-by-step explanation:
is there any diagram included about this question
someone please help me please and thank you
Answer:
it is the second one
Step-by-step explanation:
if you rotate it by 180 degrees then it will end up across the original and it will look upside down. after you rotate it dilate it by 1/2 which will look smaller than the original. after you dilate it it should be across the orriginal and upside down and be smaller than the original.
Solve & Share
Evaluate the expression 3+ (6 – 2) X 4.
Solve this problem using the order of operations.
3 + (6 – 2) X 4
Answer:
[tex]19[/tex]
Step-by-step explanation:
[tex]3 + (6 -2) \times 4[/tex]
[tex]3 + (4) \times 4[/tex]
[tex]3 + 16[/tex]
[tex]=19[/tex]
Answer:
19
Step-by-step explanation:
use the other of operations
A rectangle has a length 3x-1 and a width 2x. What is the perimeterof the rectangle
The perimeter of rectangle is 10x-2
please see the attached picture for full solution
Hope it helps
Good luck on your assignment...
Answer:
10x-2
Step-by-step explanation:
We know the length is 3x-1. There are two lengths in a rectangle. Therefore, we multiply 3x-1 by 2 to get 6x-2. That is the sum of the two lengths.
Now for the width. Just as with the length there are two widths in a rectangle. After multiplying 2x by 2, we get 4x. That is the sum of the two widths.
To get the perimeter, we need to add both the lengths and both the widths together. Using what we did before, we add 4x + 6x - 2 to get 10x - 2 Hope this helps :)
x-y+z for x= 1,y=6,z=1
Answer:
-4
Step-by-step explanation:
1-6+1=-4
Answer:
The answer is (2, -1, 3)
Step-by-step explanation:
Hope this helped.
Can someone please help me answer this question?
Answer:
132.5 inches
Step-by-step explanation:
The area of a triangle is 1/2 base height. the area of a rectangle is base height. Applying those principles gives us two equations: 8.5 x 10 / 2, and 9 x 10
then we have 42.5 and 90. in order to find the entire figure, they must be added so 42.5 plus 90 is 132.5. make sure to add the unit!
Answer:
Step-by-step explanation:
Triangle area
A=h_b*b/2
=8.5*10/2
=42.5in^2
Rectangle area
A=lw
=9*10
=90
Add all together
42.5+90
=132.5in^2
let z - 2 be an odd integer, is z+1 odd or even? explain
Answer:
Even
Step-by-step explanation:
If z-2 is an odd integer, that means z itself is an odd integer because very other integer is odd. Next, an odd integer + 1 is always an even integer. Therefore, z + 1 is an even integer.
Solve for x: 6x + 5 = 4x + 51
Answer:
x=23
Step-by-step explanation:
6x + 5 = 4x + 51
Take away 4x from both sides
2x + 5 = 51
Take away 5 from both sides
2x = 46
Divide both sides by 2
x=23
Answer: x=23
explanation: First thing you need to do is rearrange the equation so that like-terms are together. To avoid negative numbers, subtract 5 from both sides of the equation (subtraction property of equality), and subtract 4x from both sides (subtraction property of equality). You're equation would then be 2x=46. Divide both sides (division property of equality) by 2 to isolate your variable of x. You'll be left with a final answer of x=23.
Find two consecutive whole numbers that square root 2 lies between.
Answer:
1 can be written as √1 and 2 can be written as √4 and because 1 < 2 < 4, our answer is 1 and 2.
Diana and marie went out for lunch. Their Food and beverages cost $26.00 and there is an 8% meals tax. How much do they pay in total? Show your work.
6) Name all factors of x3 – 3x2 – 10x.
A. x
B. x + 5
C. x – 5
D. x + 2
E. x – 2
F. 2
G. 5
H. None of the above
its not on edg
Answer:
A. x
C. x – 5
D. x + 2
Step-by-step explanation:
From the question above, we are asked to find the factors of an algebraic expression that is given as:
x³ - 3x² - 10x
We would use the step of factorisation
Step 1
x(x² - 3x- 10)
The first factor of the algebraic expression has been obtained = x
Step 2
We factorise x² - 3x - 10
x² +2x - 5x - 10
(x²+2x) - (5x - 10)
x(x + 2) -5(x + 2)
(x + 2)(x - 5)
Step 3
x³ - 3x² - 10x
x(x² - 3x- 10)
(x)(x + 2)(x - 5)
Therefore, the factors of the algebraic expression are:
(x), (x + 2), (x - 5)